Rekonseptualisasi Nusyuz dan Syiqaq di Era Digital: Analisis Problematika dan Mekanisme Penyelesaian Modern: Penelitian - Firdaus, M. Ridho; Nelli, Jumni (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The concepts of nusyuz (disobedience of husband or wife) and syiqaq (escalating disputes) are fundamental frameworks in the jurisprudence of munakahat for analyzing and resolving domestic conflicts. However, existing literature tends to focus on the conventional manifestations of these two concepts. This study aims to reconceptualize nusyuz and syiqaq in the context of the digital era, which has given rise to new forms of problematic issues. Using conceptual analysis methods based on primary sources of Islamic law and contemporary social theories, this article identifies and categorizes forms of